Expression of MHC I Isoforms in Bovine Placentomes: Impact of Cloning - Barreto, Rodrigo da Silva Nunes [UNESP]; Mançanares, Ana Carolina Furlanetto; Miglino, Maria Angelica; Meirelles, Flávio Vieira; Oliveira, Lilian de Jesus (MDPI, 2025)
Major histocompatibility complex class I (MHC-I) gene expression in the placenta is modulated to tailor the maternal immune response to fetal antigens during pregnancy. This study evaluated MHC-I expression through immunohistochemistry (IHC) using an anti-mouse preimplantation embryo development (PED) clone Qa-2 and anti-bovine leukocyte antigen I (BoLA) monoclonal antibody clone IL-A88 (n = 23), as well as RT-qPCR (n = 17) for classical and non-classical (BoLA-NC) genes in control and cloned bovine placentomes during early and near-term gestation. Control samples showed minimal Qa-2 protein expression in early gestation, with intense labeling in trophoblasts and the maternal uterine epithelium near term. In contrast, cloned samples exhibited intense Qa-2 labeling in both maternal and trophoblastic epithelia at both stages, while trophoblast giant cells (TGCs), located apposed to the maternal epithelium, showed no labeling. Control samples exhibited intense IL-A88 labeling in the maternal epithelium at both stages. In cloned samples, weak to no labeling was observed in early gestation, with intense labeling in maternal and fetal epithelium near term. RT-qPCR revealed significant upregulation of BoLA-NC3 in early gestation, with sustained elevated expression in cloned samples in the near term. These findings suggest that altered BoLA protein expression and gene regulation in cloned pregnancies may contribute to pregnancy complications and increased losses.
Keywords: BoLA; bovine placenta; chorionic villi; cloned bovine; IL-A88; Qa-2